ANALISIS PENGGUNAAN E-FILING BERDASARKAN KEMUDAHAN DAN MINAT PERILAKU WAJIB PAJAK ORANG PRIBADI - Mulyani, Hani Sri; Sudirno, Dadang; Purnamasari, Nadya (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The use of e-filing that occurred from 2016-2020 continues to increase, this is because SPT reporting using e-filing can speed up and save resources that must be spent. However, there are still obstacles for taxpayers including taxpayers still having difficulty using e-filing and taxpayers feeling e-filing is difficult to access because not everyone can access e-filing due to unsupported networks. This study aims to examine the effect of convenience and interest on the behavior of individual taxpayers on the use of e-filing on individual taxpayers at KP2KP Majalengka. The research population is individual taxpayers at KP2KP Majalengka who have a normal/valid NPWP. Determination of the research sample by non-probability sampling that is purposive sampling based on several criteria. The research sample is 100 respondents. The tests include validity and reliability tests. This data analysis technique includes classical assumption test, multiple linear regression analysis, coefficient of determination analysis, hypothesis testing with t test and F test. The results of the study show that convenience and behavioral interest partially affect the use of e-filing significantly.